Programmed Cell Death - Gali-Muhtasib, Hala; Nasser Rahal, Omar (IntechOpen, 2020)
This book incorporates developments in our understanding of cell death mechanisms and highlights recent advances in programmed cell death regulation processes. It provides the reader with the network of pathways targeted by herbal anticancer drugs and discusses the role of endoplasmic reticulum stress in cell death mechanisms in addition to highlighting the mechanisms of autophagy and its role in diseases. This book provides valuable material for researchers and for teaching postgraduate students. Emphasis on recent advances and their clinical applications offers insights to researchers that will likely lead to the development of novel therapeutic approaches.